Professor Stuart's Postscript to his Letter to the Editors of the Biblical Repertory - Anonymous, Anonymous (Analecta Gorgiana, 2010)
The article responds to a postscript from a letter to the editor on the journal's position on loans by the American Education Society. The editor counters the writer's claims and defends the journal's prior position